TEACHERS' PERCEPTIONS IN IMPLEMENTING THE MERDEKA CURRICULUM: A SURVEY STUDY OF JUNIOR HIGH SCHOOL MUSIC TEACHERS - Puri, Tia Destiana; Narawati, Tati; Budiman, Agus (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
Abstract: The Merdeka Curriculum, introduced in 2021 in Indonesia, provides flexibility in teaching, especially in developing students' creativity and skills. Its success depends on teachers' perceptions, which reflect their understanding, assessment, and response to this policy. In the context of music, teachers must understand the objectives, principles, and implementation of the curriculum and its impact on student learning. This study explores the perceptions of junior high school music teachers in Bogor District in understanding and implementing the Merdeka Curriculum, including the challenges they face. Although this curriculum offers flexibility, teachers still face obstacles such as a lack of training and supporting resources. This study aims to obtain data and information related to how teachers perceive understanding and implementing the Merdeka Curriculum. This study uses a survey research method involving 20 music teachers in junior high schools in Bogor District. Data was collected through questionnaires and analyzed using descriptive statistical techniques. The results showed that teachers have a good understanding of the Merdeka Curriculum, but still need more training and technical support. The majority of teachers believe that this curriculum can increase student creativity if supported by adequate resources. The study concluded that music teachers' perceptions of the Merdeka Curriculum are generally positive, but implementation in the field requires increased technical support and more intensive training.Abstrak: Kurikulum Merdeka yang diperkenalkan sejak 2021 di Indonesia memberikan fleksibilitas dalam mengajar, terutama dalam mengembangkan kreativitas dan keterampilan siswa. Keberhasilannya bergantung pada persepsi guru, yang mencerminkan pemahaman, penilaian, dan respons mereka terhadap kebijakan ini. Dalam konteks seni musik, guru harus memahami tujuan, prinsip, serta implementasi kurikulum dan dampaknya pada pembelajaran siswa. Penelitian ini mengeksplorasi persepsi guru seni musik SMP di Kabupaten Bogor dalam memahami dan menerapkan Kurikulum Merdeka, termasuk tantangan yang mereka hadapi. Meskipun kurikulum ini menawarkan fleksibilitas, guru masih menghadapi kendala seperti kurangnya pelatihan dan sumber daya pendukung. Penelitian ini bertujuan untuk memperoleh data dan informasi terkait dengan bagaimana persepsi guru dalam memahami dan mengimplementasikan Kurikulum Merdeka. Penelitian ini menggunakan metode penelitian survey yang melibatkan 20 guru seni musik di SMP Kabupaten Bogor. Data dikumpulkan melalui kuesioner dan dianalisis dengan teknik statistik deskriptif. Hasil penelitian menunjukkan bahwa guru memiliki pemahaman yang baik tentang Kurikulum Merdeka, namun masih membutuhkan lebih banyak pelatihan dan dukungan teknis. Mayoritas guru percaya bahwa kurikulum ini dapat meningkatkan kreativitas siswa jika didukung dengan sumber daya yang memadai. Studi ini menyimpulkan bahwa persepsi guru musik terhadap Kurikulum Merdeka secara umum positif, namun implementasi di lapangan membutuhkan peningkatan dukungan teknis dan pelatihan yang lebih intensif.